FIELD STUDIES TO EVALUATE THE POTENTIAL OF BIOGAS AT THE LANDFILL MUNICIPAL SOLID WASTE OF UKRAINE - , А. Ю., Д. В., Ю. Б. (Municipal economy of cities. Series: «Economy science», 2013)
Paper presents analysis of some existing methods for field investigation of landfill gas generation potential at municipal solid waste landfills and provides results of investigation of LFG generation at four Ukrainian landfills.